Challenges in conserving Intangible Cultural Heritage in Vietnam as seen from the Van Phuc Silk Village - Son, Nguyen Huu (Center for Southeast Asian Social Studies (CESASS), 2023)
Traditional handicrafts in Ha Dong, Van Phuc, Vietnam, are the subject of this study. Crafts are portable and manufactured by craftsmen with artistic and manual talents, serving immediate demands and are traded and exchanged. They may exhibit cultural significance and symbolic values of gender, age, ethnicity, and nationalism, forming part of social and religious beliefs. Unfortunately, growing industrialization, globalisation, and commodification have limited them. The Van Phuc village is a great case study for how it survived and developed during urbanisation and industrialization. Applying qualitative research, data was collected through offline observations, interviews, and document analysis from 2017-2021. This study found that lack of basic infrastructure, less competitive products, traditional crafts style, and anxiety for future succession have inhibited the village's promotion of its values. To help stakeholders understand and safeguard the village, some implications are proposed.